THE TERNOPIL EDUCATIONAL COMMUNICATION CENTER: A NATO PROJECT TO INTEGRATE REGIONAL INFORMATION TECHNOLOGY RESOURCES - Markowsky, George; Sachenko, Anatoly; Voznyak, Serhiy; Spilchuk, Viktor; Romanyak, Roman; Turchenko, Volodymyr; Romanets, Ihor (International Journal of Computing, 2014)
The Ternopil Educational Communication Center was developed with NATO funding to improve computing for the universities of Ternopil, Ukraine. It provides high speed access for all of Ternopil’s universities to the Internet and the World Wide Web. It enables high speed communication within Ternopil, and between institutions in Ternopil using the UarNet and URAN networks. It provides an integration of on-line library services, and it supports such activities as video conferencing, distance education, and class to class participation. The universities of Ternopil and the University of Maine are developing programs and projects to involve students and faculty both in Ukraine and the US.